The Analysis on the Elements of Fitzgerald’s Novel the Great Gatsby and Its Application in Teaching Reading - Juita Triana (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2019)
This writing is based on the research of analyzing the elements of fitzgerald’s novelthe great Gatsby. This research is included in descriptive qualitative research. Theresearcher chooses the novel since it is about American, the English nativespeaker, for its application to English educational interests, especially teachingreading. The findings tell us that the story takes place at some parts of America.Since its theme is about love, it will inspire everybody in his/her era. Through thefirst person point of view, the author conveys the plot nicely.